Clinical and Genetic Characterization of Craniosynostosis in Saudi Arabia - Alghamdi, Malak; Alhumsi, Taghreed R.; Altweijri, Ikhlass; Alkhamis, Waleed H.; Barasain, Omar; Cardona-Londoño, Kelly J.; Ramakrishnan, Reshmi; Guzmán-Vega, Francisco J.; Arold, Stefan T.; Ali, Ghaida; Adly, Nouran; Ali, Hebatallah; et al. (Frontiers in Pediatrics, 2021)
Background: Craniosynostosis (CS) is defined as premature fusion of one or more of the cranial sutures. CS is classified surgically as either simple or complex based on the number of cranial sutures involved. CS can also be classified genetically as isolated CS or syndromic CS if the patient has extracranial deformities. Currently, the link between clinical and genetic patterns of CS in the Saudi population is poorly understood. Methodology: We conducted a retrospective cohort study among 28 CS patients, of which 24 were operated and 4 were not. Clinical and genetic data were collected between February 2015 and February 2019, from consenting patient’s families . The electronic chart data were collected and analyzed including patient demographics, craniofacial features, other anomalies and dysmorphic features, operative data, intra cranial pressure (ICP), parent consanguinity and genetic testing results. Results: The most common deformity in our population was trigonocephaly. The most performed procedure was cranial vault reconstruction with fronto-orbital advancement, followed by posterior vault distraction osteogenesis and suturectomy with barrel staving. Genetics analysis revealed pathogenic mutations in FGFR2 (6 cases), TWIST1 (3 cases), ALPL (2 cases), and TCF12 (2 cases), and FREM1 (2 case). Conclusion: Compared to Western countries, our Saudi cohort displays significant differences in the prevalence of CS features, such as the types of sutures and prevalence of inherited CS. The genomic background allows our phenotype-genotype study to reclassify variants of unknown significance. Worldwide, the sagittal suture is the most commonly affected suture in simple CS, but in the Saudi population, the metopic suture fusion was most commonly seen in our clinic. Further studies are needed to investigate the characteristics of CS in our population in a multicenter setting.